Assessment of Metal Contamination in Soils Across Roadside, Residential, and Agricultural Sites in Sri Ganganagar: A Physico-Chemical and Seasonal Analysis (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Aim: This study aimed to assess the seasonal variation of metal contamination in soils across roadside, residential, and agricultural sites in the Sri Ganganagar region. The research focused on analyzing the physico-chemical properties, including moisture content, bulk density, and metal concentrations (zinc and copper), to understand the impact of vehicular emissions on soil quality.